Assessment of Surface Tension and Viscosity of In-Zn melt - Koirala, R. P.; Yadav, S. K.; Singh, B. P.; Jha, I. S.; Adhikari, D (Himalayan Physics, 2017)
A comparative study of the concentration dependence of surface tension and viscosity of molten In-Zn alloys at 700 K has been performed using energetics, obtained from thermodynamic analysis in the framework of self-association model. The surface tension of the alloys has been calculated from the two methods, layered structure approach and self associating mixture method, and viscosity from Moelwyn-Hughes equation and Kaptay equation. The theoretically computed results for the thermodynamic properties of the alloys are found in excellent agreement with the corresponding experimental results showing that the alloy is segregating in nature. Both surface tension and viscosity of the In-Zn alloy are found to increase with the addition of Zn atoms. The Himalayan Physics Vol. 6 & 7, April 2017 (15-19)